COMMON GRAMMATICAL ERRORS MADE BY UZBEK EFL LEARNERS: CAUSES AND PEDAGOGICAL SOLUTIONS - Zokirova Marjona Xislatjon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation : This paper investigates the most frequent grammatical errors made by Uzbek learners of English as a Foreign Language (EFL), analyzing their underlying causes and proposing effective pedagogical solutions. Drawing on data collected from student writing samples, classroom observations, and teacher interviews, the study categorizes common errors related to verb tense, articles, prepositions, and sentence structure. It explores the influence of first language (L1) interference, lack of grammar awareness, and inadequate teaching practices. The paper also outlines classroom strategies and corrective techniques aimed at minimizing these errors and improving grammatical accuracy in Uzbek EFL contexts.